Nonlinear Dynamics in Geosciences
DOI: 10.1007/978-0-387-34918-3_25
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from Wavelet Lag Coherence for Negligible Solar Forcing of Climate at Multi-year and Decadal Periods

Abstract: Abstract. We examine possible links between solar cycle irradiance variations the large atmospheric circulation systems that affect whole planet's climate. In particular we examine the putative mechanism of solar forcing mediated by changes in induced stratospheric conditions over the polar regions. We test this hypothesis by examining causal links between time series of solar irradiance based on both amplitude and length of the 11-year solar sunspot cycle and indices of Arctic Oscillation AO and ENSO activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(22 reference statements)
2
4
0
Order By: Relevance
“…What that data lacks in duration compared to the Central England Temperature record (Johnson, 2009a(Johnson, , 2010a it more than makes up for in breadth of geophysical location. We note that our results are in accord with other investigators (Friis-Christensen and Lassen, 1991;Lean and Rind, 1998;Echer et al, 2009) and contrast with those who have found negligible evidence of solar forcing on Earth's climate (Moore et al, 2006(Moore et al, , 2007Lockwood and Fröhlich, 2007;Li et al, 2009). Most authors, when speaking of the influence of solar forcing on Earth's climate, are actually discussing the effect of changing some model parameters in a simulation of meteorological systems (Shindell et al, 2003;Wagner and Zorita, 2005), whereas here we are discussing a correlation found between independent instrumental observations from the historical record.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…What that data lacks in duration compared to the Central England Temperature record (Johnson, 2009a(Johnson, , 2010a it more than makes up for in breadth of geophysical location. We note that our results are in accord with other investigators (Friis-Christensen and Lassen, 1991;Lean and Rind, 1998;Echer et al, 2009) and contrast with those who have found negligible evidence of solar forcing on Earth's climate (Moore et al, 2006(Moore et al, , 2007Lockwood and Fröhlich, 2007;Li et al, 2009). Most authors, when speaking of the influence of solar forcing on Earth's climate, are actually discussing the effect of changing some model parameters in a simulation of meteorological systems (Shindell et al, 2003;Wagner and Zorita, 2005), whereas here we are discussing a correlation found between independent instrumental observations from the historical record.…”
Section: Discussionsupporting
confidence: 85%
“…The amount of influence which the solar magnetic cycle has on Earth's climate continues to be a matter of debate (Lean and Rind, 1998;Wagner and Zorita, 2005;Moore et al, 2006Moore et al, , 2007Lockwood and Fröhlich, 2007;Echer et al, 2009;Li et al, 2009;Sitnov, 2009). The intriguing coincidence of the Maunder Minimum (Eddy, 1976;Luterbacher et al, 2001), a period of exceptionally low solar activity as indicated by a dearth of sunspots observed from 1645 and 1715, and the coldest years of the Little Ice Age (Grove, 2001;Mann, 2002), a period of exceptionally low temperatures as observed in Europe, North America, and elsewhere (Kreutz et al, 1997;Johnson et al, 2001;Holmgren et al, 2001) ending in the middle of the 19th century, suggests that the temperature on Earth might display a dependence on the level of solar magnetic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Here we find the linear trend holds up until about 1990, after which the observed temperature increases without relation to the magnetic activity. We note that our results are in accord with other investigators [27,28,10] and contrast with those who have found negligible evidence of solar forcing on Earth's climate [29,30,31].…”
Section: Analysis Of the Datasupporting
confidence: 90%
“…The properties of our transform menagerie are summarized in Table 2. Let us first consider the responses of the EAWT, the AAWT, and the CCWT to a succession of test signals y k of duration N t = 300 with squared amplitudes A 2 k = [1, 2, 3, 4] and periods P k = [5,30,150,300]. In Figure 10 we display the IIP for each test signal.…”
Section: Comparison Of the Adapted Transformsmentioning
confidence: 99%
“…We used the Paul wavelet (order 4) as it is not very localized in frequency space and allows signals that are relatively aperiodic to be included in the analysis (Moore et al. ). The statistical significance level (90%) of the WTC against red noise backgrounds was estimated using Monte Carlo methods with n = 1000 iterations.…”
Section: Methodsmentioning
confidence: 99%